2021
DOI: 10.3390/data6080088
|View full text |Cite
|
Sign up to set email alerts
|

VHR-REA_IT Dataset: Very High Resolution Dynamical Downscaling of ERA5 Reanalysis over Italy by COSMO-CLM

Abstract: This work presents a new dataset for recent climate developed within the Highlander project by dynamically downscaling ERA5 reanalysis, originally available at ≃31 km horizontal resolution, to ≃2.2 km resolution (i.e., convection permitting scale). Dynamical downscaling was conducted through the COSMO Regional Climate Model (RCM). The temporal resolution of output is hourly (like for ERA5). Runs cover the whole Italian territory (and neighboring areas according to the necessary computation boundary) to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Our work is a first assessment about the reliability, affordability and ease of implementation of the BOLAM/MOLOCH suite for downscaling reanalyses and thus, potentially, climate projections. Furthermore, thanks to the numerous ongoing activities regarding the refinement of ERA5 data at the local scale, the BOLAM/MOLOCH hindcast can complement similar datasets (Bonanno et al, 2019;Raffa et al, 2021b) to create a multi-model and convection-permitting ensemble, aimed at assessing the uncertainty of past climate in Italy. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work is a first assessment about the reliability, affordability and ease of implementation of the BOLAM/MOLOCH suite for downscaling reanalyses and thus, potentially, climate projections. Furthermore, thanks to the numerous ongoing activities regarding the refinement of ERA5 data at the local scale, the BOLAM/MOLOCH hindcast can complement similar datasets (Bonanno et al, 2019;Raffa et al, 2021b) to create a multi-model and convection-permitting ensemble, aimed at assessing the uncertainty of past climate in Italy. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing rainfall outputs with the E-OBS (Cornes et al, 2018) gridded dataset as ground truth, the authors argued that the direct nesting should be preferred. In a second paper (Raffa et al, 2021b), the authors presented the dataset, which covers the Italian domain, for the period 1989-2020. More recently, Reder et al (2022), demonstrated that this dataset provides more reliable data than global reanalyses in characterising extreme precipitations at the urban scale.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported multiple benefits related to increased grid resolutions in numerical simulations, allowing an adequate representation of local dynamical features and forcings leading to or intensifying precipitation events (Buzzi et al ., 2014; Cassola et al ., 2015; Clark et al ., 2016; Wahl et al ., 2017; Klasa et al ., 2018; Cerenzia et al ., 2020; Capecchi, 2021). Furthermore, the results obtained are in line with those of recently produced CP hindcasts over Italy, sharing similar characteristics with SPHERA, and obtained by downscaling ERA5 with the BOLAM/MOLOCH model (Capecchi et al ., 2022) or COSMO model (Raffa et al ., 2021; Reder et al ., 2022). In Capecchi et al .…”
Section: Discussionmentioning
confidence: 99%
“…When coming to Italy, the considerable interest in developing highly resolved re-forecast datasets is demonstrated by the recent production of two CP regional hindcasts. These are obtained by downscaling ERA5 using the COSMO model at 2.2 km grid spacing (Raffa et al, 2021;Reder et al, 2022) or the model MOLOCH at 2.5 km (Capecchi et al, 2022). Anyhow, in neither case is the additional assimilation of regional observations included in the production of the datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, as part of the Highlander project ( https://highlanderproject.eu/ ), Raffa et al . 15 released VHR-REA_IT (Very High-Resolution REAnalysis for ITaly), a gridded dataset for the recent past thirty years (1989–2020) over Italy. Such a dataset has been obtained by dynamically downscaling ERA5 reanalysis 16 from its native resolution (≃31 km) to a resolution of ≃2.2 km using the regional climate model COSMO-CLM 17 .…”
Section: Background and Summarymentioning
confidence: 99%